2017
DOI: 10.4012/dmj.2016-394
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low polymerization shrinkage flowable resin composites in newly-developed cavity base materials for bulk filling technique

Abstract: The purpose of this study was to evaluate polymerization shrinkage and other physical properties of newly-developed cavity base materials for bulk filling technique, with the brand name BULK BASE (BBS). Polymerization shrinkage was measured according to ISO/FDIS 17304. BBS showed the significantly lowest polymerization shrinkage and significantly higher depth of cure than conventional flowable resin composites (p<0.05). The Knoop hardness, flexural strength and elastic modulus of that were significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…%. Nitta et al [24] reported values for inorganic FRC filler between 45.4 and 64.7 wt. % using the same method.…”
Section: Discussionmentioning
confidence: 99%
“…%. Nitta et al [24] reported values for inorganic FRC filler between 45.4 and 64.7 wt. % using the same method.…”
Section: Discussionmentioning
confidence: 99%
“…Shrinkage is widely recognized as an inherent phenomenon in polymerizable monomer resins when polymerization occurs [ 18 , 19 , 20 ]. There have been different methods to measure the volumetric shrinkage of composite resins, such as the use of the mercury dilatometer, the Archimedes method, and the video imaging method [ 44 , 45 , 46 , 47 , 48 ]. AcuVol is a video imaging measurement system that allows for noncontact visual analysis of volume changes in small-volume samples, and it determines volumetric shrinkage in real time based on optical measurements and pattern recognition [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased light intensity can be compensated for by extending the irradiation time. In the clinical situation, it is important to use a longer irradiation time for the polymerization of cavity base materials [ 41 ]. Another aspect was examined when Zn-doped glass was incorporated in flowable composite for enhancing its antimicrobial character; no significant difference in the DoC between groups was noticed, meaning that the incorporation of Zn-doped glass did not affect the polymerization of the composite [ 25 ].…”
Section: Development Of Discussionmentioning
confidence: 99%